2020
DOI: 10.21608/ijma.2020.23053.1138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Successful Direct Acting Antivirals Therapy on Liver Stiffness in Patients with Chronic HCV Infection

Abstract: Background: Achievement of sustained virological response [SVR] and improvement of hepatic fibrosis are the essential goals for therapy of chronic hepatitis C [CHC] with direct acting antivirals [DAAs] therapy. Early detection and management of hepatic fibrosis can significantly improve the prognosis of CHC in clinical practice. Aim of the work: To assess the effect of successful DAAs therapy on liver stiffness in patients with CHC. Methods: This study included 100 patients with chronic HCV-related liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Lee SH, 2020, who studied 68 patients with chronic HCV infection and reported that SWE findings showed significant improvement in LSM after 12-week SVR [22]. Also, Serkan et al, 2020, and Ezzelregal, 2020, found a significant regression in the LSM of CHC patients receiving DAA therapy using SWE that carried out at the start of treatment, EOT, and 12 weeks after EOT [23,24]. On the other hand, Ekaterinea et al, 2017, evaluated the effect of DAA therapy on liver fibrosis regression measured by transient elastography in CHC patients and reported decline in the median liver stiffness at week 24 after treatment compared with baseline but despite decreased LS, more than half of the cirrhotic patients with LS remained cirrhotic at week 24 following treatment [25].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Lee SH, 2020, who studied 68 patients with chronic HCV infection and reported that SWE findings showed significant improvement in LSM after 12-week SVR [22]. Also, Serkan et al, 2020, and Ezzelregal, 2020, found a significant regression in the LSM of CHC patients receiving DAA therapy using SWE that carried out at the start of treatment, EOT, and 12 weeks after EOT [23,24]. On the other hand, Ekaterinea et al, 2017, evaluated the effect of DAA therapy on liver fibrosis regression measured by transient elastography in CHC patients and reported decline in the median liver stiffness at week 24 after treatment compared with baseline but despite decreased LS, more than half of the cirrhotic patients with LS remained cirrhotic at week 24 following treatment [25].…”
Section: Resultsmentioning
confidence: 99%